PROGRAM KEMITRAAN MASYARAKAT PELATIHAN PERPUSTAKAAN DIGITAL DI SMAN 2 ABIANSEMAL BADUNG - I Made Subrata; I Kadek Juni Arta; I Dewa Putu Juwana; I Made Surat (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
School digital library training can be carried out to provide understanding and skills to school library managers in managing libraries digitally. The aim of this PkM is to provide assistance to teachers and school library staff so they can use the school digital library. The method for implementing PkM is preparation, implementation, monitoring and evaluation and follow-up. The use of digital technology in school libraries can provide various benefits for students and teachers. School libraries utilizing digital technology can become more modern and effective learning centers. The PerpusKita.id application is a library automation system developed by the National Library of the Republic of Indonesia to simplify library management, starting from cataloging, circulation, to reporting. This training is designed to provide practical and technical understanding to librarians. Many teachers and students can search for information online through search sites, but it is difficult for students to determine which books can be referred to and used regarding the material taught by the teacher or information related to the information obtained. With training and assistance from UPMI lecturers' PkM activities, it is hoped that the digital library can become a center for developing and advancing literacy quality that is beneficial for all levels of the school community. The school digital library used can be accessed from anywhere and at any time via the link provided to log in to the Digital Library.